2021
DOI: 10.1007/s10557-021-07193-z
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Reverses Nitroglycerin Tolerance through Suppressing Protein Kinase C Alpha Activity in Vascular Smooth Muscle Cells

Abstract: The aim of the present study was to evaluate the effects of berberine on nitroglycerin (NTG) tolerance and explore the underlying mechanism involved. MethodsNTG tolerance was induced by pre-exposure of Sprague-Dawley rat aortas to NTG in vitro or by pretreating Sprague-Dawley rats with NTG patch in vivo. The aortas were pre-treated with berberine or PKC inhibitors for different durations of time before induction of NTG tolerance. NTG-induced vasorelaxations was measured on wire myograph. Primary vascular smoot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…NO has a vasodilator function, so nitroglycerin has been used in clinical treatment for many CVDs, such as angina pectoris, congestive heart failure, and myocardial infarction. Berberine administration in rats could suppress protein kinase C-α in VSMCs to reverse nitroglycerin tolerance caused by long-term use (Zhang et al, 2021). All these results suggest that berberine may be latently available to prevent restenosis of arteries by inhibiting VSMCs proliferation.…”
Section: Berberine's Curative Effects On Vsmcsmentioning
confidence: 84%
See 1 more Smart Citation
“…NO has a vasodilator function, so nitroglycerin has been used in clinical treatment for many CVDs, such as angina pectoris, congestive heart failure, and myocardial infarction. Berberine administration in rats could suppress protein kinase C-α in VSMCs to reverse nitroglycerin tolerance caused by long-term use (Zhang et al, 2021). All these results suggest that berberine may be latently available to prevent restenosis of arteries by inhibiting VSMCs proliferation.…”
Section: Berberine's Curative Effects On Vsmcsmentioning
confidence: 84%
“…Many traditional herbs inhibit the phenotype switching of VSMCs in atherosclerosis; examples include chocolate vine, garlic, and mountain asparagus (Saleh Al-Shehabi et al, 2016). Numerous studies have shown that berberine inhibited VSMCs proliferation and migration induced by multiple stimuli (Fatahian et al, 2020;Wu et al, 2020;Zhang et al, 2021), but whether berberine could inhibit the switching of VSMCs from contractile to synthetic phenotypes to reduce atherosclerosis has not been reported and must be explored.…”
Section: Berberine's Curative Effects On Vsmcsmentioning
confidence: 99%